Simulasi Pengaruh Ukuran Butir (Grain Size) terhadap Tingkat Kekuatan (Strength) Aluminium Nanostruktur Menggunakan Metode Dinamika Molekul - Pristia Eka Kurniawati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Aluminum is one of the most widely used engineering materials due to its low density, excellent corrosion resistance, and high strength-to-weight ratio. At the nanoscale, the mechanical properties of aluminum are significantly influenced by microstructural parameters, particularly grain size. Variations in grain size affect the distribution of grain boundaries, which play an important role in determining the deformation behavior and strength of nanostructured materials. Therefore, this study aims to investigate the effect of grain size on the mechanical properties of nanostructured aluminum, specifically Young’s Modulus and Ultimate Tensile Strength (UTS), using Molecular Dynamics (MD) simulations. The simulations were performed using the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS). Aluminum models were constructed in single-crystal and polycrystalline forms with grain sizes of 3 nm, 5 nm, 10 nm, and 20 nm. Interatomic interactions were described using the Embedded Atom Method (EAM) potential. Uniaxial tensile tests were conducted to obtain stress–strain curves, from which Young’s Modulus and UTS values were determined. Structural analysis and visualization of grain boundaries were carried out using Python, while the relationship between grain size and mechanical properties was evaluated through linear regression analysis. The results show that single-crystal aluminum exhibits a Young’s Modulus of 63.10 GPa and a UTS of 8.07 GPa. Polycrystalline aluminum demonstrates higher mechanical performance, with the highest values obtained at a grain size of 3 nm, yielding a Young’s Modulus of 114.57 GPa and a UTS of 9.25 GPa. As grain size increases, both Young’s Modulus and UTS tend to decrease. Linear regression analysis reveals a negative correlation between grain size and UTS with a coefficient of determination (R²) of 0.938. These findings indicate that smaller grain sizes enhance the mechanical strength of nanostructured aluminum due to the increased contribution of grain boundaries in resisting deformation during tensile loading.
FINALISASI oleh Arif 2026 Juni 24
Keywords: Aluminum Nanostructure; Grain Size; Grain Boundary; Molecular Dynamics; Young’s Modulus; Ultimate Tensile Strength; LAMMPS.